Characteristics of Ground-Glass Nodules Detected by Low-Dose Computed Tomography as a Regular Health Examination Among Chinese Hospital Employees and Their Parents - Bihan Ouyang; Maoyuan Li; Li Li; Shaohui Liu; Min Li; Min Li; Min Li; Min Li (Frontiers in Oncology, 2021)
IntroductionAnnual LDCT has been offered as a regular examination among many unit staff in China. Along with the wide application of LDCT, more and more ground-glass nodules were found. We focused on characteristics and relationship of ground-glass nodules detected by LDCT as a regular health examination among Chinese hospital employees and their parents.MethodsWe recorded LDCT-detected ground-glass nodules (GGNs) in the hospital employees and parents between 2019 and 2020. Clinical information, including age, gender, smoking status was collected and analyzed.ResultsA total of 5,574 employees and 2,686 employs’ parents ≥60 years in Xiangya hospital performed annual physical examination. In total, LDCT incidentally detected ground-glass nodules 392 (24.78%, 392/1,582) in hospital employees and 254 in parents (10.80%, 254/2,352). The GGN-detection rate was significantly greater in employee group than parent group and more non-smokers in former (P <0.001). The detection rate was significantly greater in female than male both in employees group and parents group, and the proportion of female was bigger in employees group (P <0.001). There were more pure-GGNs both in employees group and parents group. There were less participants with solitary GGN in employee group than parent group (P = 0.033). Besides, there were more large GGNs (≥10 mm) (P <0.001), LU-RADS 4 GGNs (P <0.001) and LU-RADS 4B GGNs (P = 0.003), LU-RADS 4C-5 GGNs (P = 0.001) in parent group than employee group. There were 36 employee–parent pairs (27.07%) both had GGNs among 133 pairs who both performed LDCT. GGNs in employees were smaller and lower-grade than their parents (P < 0.001, P = 0.001).ConclusionsAmong the employees and parents who had ground glass nodules, 1/4 of them both detected GGNs. Although the detection rate of GGNs in the parent group was lower than that in the employee group, the grade of nodules was significantly higher. All these suggest that the occurrence and development of ground glass nodules may be related to genetic factors.